Cocofoamblocks: The potential of styrofoam and coconut fiber as paving blocks - Asarudin, Tifa Alfatiha; Wahyunita, Fitrana; Anggraini, Sarah Dwi (UIN Sunan Ampel Surabaya, 2024)
Styrofoam waste is an inorganic material that cannot decompose and will continue to accumulate if not recycled. Styrofoam has relatively light properties, can withstand heat, and is resistant to corrosives. In coastal and marine environments, styrofoam waste can cause significant pollution and damage to marine ecosystems. However, when used in the production of paving blocks, styrofoam waste has a disadvantage: it results in a low compressive strength value. To address this, coconut fibers are used to strengthen the paving blocks because coconut fibers have tensile strength, making them durable, lightweight, and elastic. The purpose of this study was to determine the mechanical properties of paving blocks made with a mixture of styrofoam and coconut fibers (Cocofoamblocks). The method used in this study is a quantitative approach with experimental research. The results of the water absorption test show that the absorption rates of the Cocofoamblocks is in the range of 17.55% to 19.28%. This indicates that the Cocofoamblocks can be categorized as suitable for use. The results of the compressive strength test show that the average value for sample BT1 is 0.5 MPa, while samples BT2 and BT3 have values of 1.1 MPa and 2.4 MPa, respectively. Based on these results, it is evident that the compressive strength of the Cocofoamblocks can be categorized as unsuitable for use. This is because the Cocofoamblocks lack coarse aggregates, and the excessive amount of water used in the mixture during production further reduces their compressive strength. This study contributes to efforts to reduce waste pollution in coastal and marine areas, as well as to creating environmentally friendly solutions that can enhance the sustainability of development in coastal regions.